Lichen indication assessment of changes in the air quality of Kherson town for the past 20 years (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The results of lichen indication research of surface layers quality of Kherson air are given in the article. 44 species of epiphytic lichens have been found, including 17 taxa identified as new to the studied area, and 11 species appeared in the last two decades. According to clean air calculation Index a spatial distribution model of izotoxic lichen indication zones of the city was built, the possible causes and patterns of their distribution in a given location were analyzed. A comparative analysis of distribution zones with different air quality for the period of 1995–2015 was conducted. Relative decrease in the dynamics and reduction of unpolluted and lightly polluted area of lichen indication izotoxic zones was observed; it is associated with changes in the intensity and sources of anthropogenic influence for the last two decades. Seven types of urban landscapes were identified and for each of them relative air quality by lichen indication detectors was set. The poorest air quality was found within vehicles landscapes that consist of 2/3 highly and moderately polluted lichen indication izotoxic zones and the highest quality – within the garden and park landscapes, where 3/4 of the territory is located on unpolluted and moderately polluted areas.
Keywords: bioindication, urban landscapes, epiphytic lichens, lichen indication zone.